Diversity of Avian Fauna in and Around Kalyani, a Sub-Urban City near Kolkata, West Bengal, India - Ghosh, Tapas; Sardar, Soumi; Sarkar, Sweata (International Journal of Scientific Research in Biological Sciences, 2024)
Avifaunal diversity has proven a crucial factor for maintaining the ecological equilibrium of any given ecosystem. The present investigation determines the avifaunal distribution, diversity and status in and around Kalyani from December 2021 to January 2023. During the appropriate study period, a total of 73 bird species belongs to 39 different families under 17 orders were reported. In agreement with the status of the bird species, 63 (86.30%) species were regional, 3 (4.11%) winter migrant, 4 (5.48%) regional migrant, 2 (2.74%) migratory and 1 (1.37%) monsoon visitor. Winter visiting species were Western yellow wagtail, Citrine wagtail and Common moorhen. Two migratory species were Common hill mayna, Sand Martin and one monsoon visitor was Jacobin cuckoo. Determining the relative abundance of the birds, 25 (34%) species were commonly seen, 31 (42%) very common, 12 (16%) uncommon but not rare and 5 (6.8%) rare. The Sturnidae (5 species) was the most diversified family in the investigation area, followed by Ardeidae, Alcedinidae, Columbidae and cuculidae (each having 4 species). The study also found seven unique feeding habits viz. 27% carnivorous, 26% insectivorous, 21% omnivorous, 11% granivorous, 9.6% frugivorous, 4.1% Nectarivorous and 1.4% Nectarivorous/Insectivorous species of bird. The current report is an attempt to chronicle the diversity of avian population in and around Kalyani and it is necessary to conduct a more through systematic research in order to investigate and safeguard the avifaunal variety within this area.